Evidence Map on the Relationship Between Dietary Sweetness Exposure and Body Weight-Related Outcomes in Adults. (14th June 2022) - Higgins, Kelly; Rawal, Rita; Baer, David; O'Connor, Lauren; Appleton, Katherine
Abstract: Objectives: An evidence map was conducted to characterize published research investigating dietary sweetness and body weight. The primary aim was to identify studies that investigate total dietary sweetness and body weight-related outcomes among healthy adults; the secondary aim was to map the evidence that investigates sugar, sweetener, or sweet food/beverage intake and body weight. Methods: Using pre-registered search terms (https://osf.io/my7pb), 33, 609 publications (duplicates removed) from PubMed, Cochrane Library, and Scopus were screened for inclusion. Eligible studies were cross-sectional studies, longitudinal cohort studies, case control studies, clinical trials, and systematic reviews conducted among adults (≥18 years) which investigated the associations between total dietary sweetness, sugar, sweetener (energetic or nonenergetic), or sweet food/beverage intake on body weight, body mass index, adiposity, and energy intake. Results: A total of 824 eligible publications were identified. Two clinical trials and 5 cross-sectional studies investigated the associations between total dietary sweetness and a body weight-related outcome. An additional 630 publications were identified that investigated sugar, sweetener, or sweet food/beverage intake and body weight-related outcomes, including 225 clinical trials, 87 longitudinal cohort studies, and 298 cross-sectional studies. Ninety publications reported on dietary patterns that included sweet foods/beverages alongside other dietary components. Most studies (91%) did not measure the sweetness of the diet or individual foods consumed. Additionally, 97 systematic reviews that addressed relevant but different research questions related to sweetness exposure and body weight-related outcomes were identified. Conclusions: While there is a breadth of evidence available from studies that investigate sugar, sweetener, and sweet food/beverage intake and body weight, there is limited evidence on the association between total dietary sweetness exposure and body weight. Funding Sources: USDA Agricultural Research Service, Institute for the Advancement of Food and Nutrition Sciences.